Corona Virus Disease 2019 and Paediatric Inflammatory Bowel Diseases: Global Experience and Provisional Guidance (March 2020) from the Paediatric IBD Porto Group of European Society of Paediatric Gastroenterology, Hepatology, and Nutrition. Issue 6 (June 2020) - Turner, Dan; Huang, Ying; Martín-de-Carpi, Javier; Aloi, Marina; Focht, Gili; Kang, Ben; Zhou, Ying; Sanchez, Cesar; Kappelman, Michael D.; Uhlig, Holm H.; Pujol-Muncunill, Gemma; Ledder, Oren; et al.
ABSTRACT: Introduction: With the current coronavirus disease 2019 (COVID-19) pandemic, concerns have been raised about the risk to children with inflammatory bowel diseases (IBD). We aimed to collate global experience and provide provisional guidance for managing paediatric IBD (PIBD) in the era of COVID-19. Methods: An electronic reporting system of children with IBD infected with SARS-CoV-2 has been circulated among 102 PIBD centres affiliated with the Porto and Interest-group of ESPGHAN. A survey has been completed by major PIBD centres in China and South-Korea to explore management during the pandemic. A third survey collected current practice of PIBD treatment. Finally, guidance points for practice have been formulated and voted upon by 37 PIBD authors and Porto group members. Results: Eight PIBD children had COVID-19 globally, all with mild infection without needing hospitalization despite treatment with immunomodulators and/or biologics. No cases have been reported in China and South Korea but biologic treatment has been delayed in 79 children, of whom 17 (22%) had exacerbation of their IBD. Among the Porto group members, face-to-face appointments were often replaced by remote consultations but almost all did not change current IBD treatment. Ten guidance points for clinicians caring for PIBD patients in epidemic areas have been endorsed with consensus rate of 92% to 100%. Conclusions: Preliminary data for PIBD patients during COVID-19 outbreak are reassuring. Standard IBD treatments including biologics should continue at present through the pandemic, especially in children who generally have more severe IBD course on one hand, and milder SARS-CoV-2 infection on the other. Supplemental digital content: An infographic accompanying this article can be found at http://links.lww.com/MPG/B842 . Abstract : Supplemental Digital Content is available in the text